2009
DOI: 10.1088/0953-8984/21/26/265502
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of C84film studied by photoemission measurement and first-principles calculation

Abstract: We have measured the photoemission spectra of a C(84) film (isomer mixture) with synchrotron radiation. The valence band exhibits abundant spectral features from the Fermi level to ∼18 eV binding energy. The relative intensity between the lowest binding energy feature (labeled as A) and the next lowest binding energy feature (labeled as B) oscillates distinctly within the experimental photon energy region from 21.0 to 63.0 eV. The energy levels and density of states (DOS) are calculated for the D(2d)(23)- C(84… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…However, the energy intervals between the occupied levels are generally (though not always) reliable. [29][30][31] spectral features between the Fermi level and 5 eV binding energy; the spectral shape is much alike the reported spectra. [7,16] Comparing Fig.…”
Section: Methodssupporting
confidence: 52%
“…However, the energy intervals between the occupied levels are generally (though not always) reliable. [29][30][31] spectral features between the Fermi level and 5 eV binding energy; the spectral shape is much alike the reported spectra. [7,16] Comparing Fig.…”
Section: Methodssupporting
confidence: 52%
“…Fortunately, we found that a simple remedy of multiplying the energy scale of the calculated results by a coefficient can eliminate the disagreement. [21,22] Figure 4(b) shows the comparison of the experimental data with the remedied TDOS whose energy scale has been multiplied by a coefficient of 1.115. After the energy correction, the TDOS coincides with the spectra very well (especially for the 2p-dominated states from the Fermi level to ∼14 eV BE, as indicated by the vertical lines).…”
Section: Resultsmentioning
confidence: 99%
“…[23] Their electronic structures are also similar. [27] We cannot expect to discriminate between them by STM measurements at room temperature.…”
Section: Pit Configurationmentioning
confidence: 99%